Право як феномен культури: спроба концептуальної самокритики. Стаття перша. Про доцільність постановки проблеми і деякі питання методології та термінології. Частина 2. Про термінологію: сталі (загальні) термінопоняття - Литвинов, О. М.; Lytvynov, O. M.; ORCID: http://orcid.org/0000-0003-2952-8258 (Вісник Луганського держаного університету внутрішніх справ ім. Е. О. Дідоренка. – 2018. – Вип. 2 (82). – С. 37-47, 2018)
Питання термінології в процесі дослідження права як феномену культури проаналізовано у взаємозв’язку з методологічними проблемами формування та здійснення культурологічного підходу у філософії права. Розглянуто ключові категорії концептуального рівня: культура, право, вторинні культури тощо. Доведено думку про необхідність апелювання до методологічних досягнень світової (західної) філософії ХХ століття, на основі яких запропоновано формування культурологічного підходу, що спирається на засадничі ідеї Аристотеля. Показано практичну доцільність і ефективність такого підходу на прикладі аналізу сучасного вітчизняного законодавства.

The questions of terminology in the process of the study of law as a cultural phenomen on are analyze dinconnection with the methodological problems of the formation and implementation of the culturological approach in the philosophy of law. The key categories of the conceptual level are considered: culture, law, secondarycultures, etc. The author proves the necessity of appealing to the methodological achievements of the world (western) philosophyofthe 20th century, on the basis of which it is proposed the formationof a culturological approach that is based on the fundamental ideas of Aristotle. Preference is given to phenomenology (and phenomenological hermeneutics), as well as ontology. The meaning of the concept of "phenomenon" as a result of ascer taining the presence of its boundaries in the ontological section through the particle "as" isconsidered. Practical expediency and efficiency of such approach is show non an example of the analysis of the modern domestic legislation. The indication in the title of the article about the appropriateness soft his angle is also an explanation of the introduction of new terms for the jurisprudence (terminology) or giving new additional meanings to the terms already available. There is no certain arbitrariness of the author, the appeal to them follows from attemptsto explain the function in goflawand, especially, it serosion in the most complicated processes of state building inpost-totalitarian societies, primarily in Ukraine. The peculiarity of this text is the clarification of the content and some meanings of the terminology, which is well established in jurisprudence, including the philosophy of law. Clarifications and explanations are the result of critical remarks made by various opponents of the author of this article. The negative significance of such a quality of culture as imitation is emphasized, which became the main reason for defining such cultures as "secondary" cultures. This is also manifested as the quality of legal culture. An attempt has been made to provide additional arguments for the separation of the concepts of legal culture and legal consciousness, which are not always clearly separated in the theory of law and state. The as sumption of the corruption component in the process of judicial reformin Ukraine was advanced on the basis of the culturological approach developed, as well as the culturological approaches in the jurisprudence of the USA (R. Pozner) and Lithuania (A. Vaishvila).

Вопросы терминологии в процессе исследования права как феномена культуры анализируются в взаимосвязи с методологическими проблемами формирования и осуществления культурологического подхода в философии права. Рассматриваются ключевые категории концептуального уровня: культура, право, вторичные культуры и т. п. Доказывается положение о необходимости апеллирования к методологическим достижениям мировой (западной) философии ХХ века, на основе которых предлагается формирование культурологического подхода, который опирается на основополагающие идеи Аристотеля. Показана практическая целесообразность и эффективность такого подхода на примере анализа современного отечественного законодательства.
Law as a Phenomenon of Culture: Attempt of Conceptual Selfcriticism. Article One. On the Appropriateness of Formulation the Problem and Some Issues of Methodology and Terminology. Part 2. On the Terminology: Set (general) Terms-Notions
Право как феномен культуры: опыт концептуальной самокритики. Статья первая. О целесообразности постановки проблемы и некоторые вопросы методологии и терминологии. Часть 2. О терминологии: устоявшиеся (общие) терминопонятия
Литвинов, О. М. Право як феномен культури: спроба концептуальної самокритики. Стаття перша. Про доцільність постановки проблеми і деякі питання методології та термінології. Частина 2. Про термінологію: сталі (загальні) термінопоняття / О. М. Литвинов // Вісник Луганського держаного університету внутрішніх справ ім. Е. О. Дідоренка. – 2018. – Вип. 2 (82). – С. 37-47.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; право; культура; Філософія. Логіка. Philosophy. Logic. Философия. Логика; Філософія права. Philosophy of law. Философия права; правознавство; феномен; феноменологія; онтологія; термінологія; вторинні культури; law; culture; philosophy of law; jurisprudence; phenomenon; phenomenology; ontology; terminology; secondary cultures; философия права; правоведение; феноменология; онтология; терминология; вторичные культуры